Analisis dan Perancangan Interoperabilitas Data Pemonitoran SPM (Standar Pelayanan Minimal) Bidang Kesehatan dengan Web Services - Farid Mahmudi (Jurnal Rekam Medis dan Informasi Kesehatan, 2023)
System  interoperability  is  a  key  factor  in  the  transformation  of  the  minimum  service  standards  (SPM)  reporting  system  in  the  health  sector.  This  article  presents  an  in-depth  analysis  to  design  an  Application  Programming  Interface  (API)  model  that  aims  to  increase  the  effectiveness  of  sending  and  reporting  SPM  data  from  primary  health  facilities  under  the  district  health  office.  Through  analytical  studies,  we  identified  system  interoperability  needs  at  the  district  health  department  level,  including  aspects  such  as  electronic  medical  record  (EMR)  data  formats,  minimum  service  standards,  and  patient  identification  systems.  One  of  the  main  challenges  is  the  diversity  of  data  formats  and  sources  that  must  be  integrated. Based  on  this  analysis,  we  designed  an  API  specifically  designed  to  facilitate  the  exchange  of  important  data  related  to  reporting  minimum  service  standards  in  the  health  sector.  The  resulting  API  follows  the  principles  of  RESTful  architecture,  prioritizing  scalability,  flexibility,  and  security.  API  specifications  include  nationally  recognized  data  standards  for  health  reporting  as  well  as  stringent  authentication  and  authorization  systems  to  protect  sensitive  data.  Initial  implementation  and  testing  results  show  that  the  proposed  API  successfully  connects  diverse  health  reporting  systems  with  high  effectiveness.  Evaluation  of  API  performance  through  measuring  response  time  and  resource  usage  indicates  adequate  performance  for  use  in  a  production  environment.  Through  the  design  of  this  API,  it  is  hoped  that  it  can  increase  interoperability  between  minimum  service  standard  reporting  systems  in  the  health  sector,  reduce  data  duplication,  and  speed  up  the  reporting  process. The  conclusions  of  this  study  underscore  the  important  role  of  APIs  in  supporting  healthcare  quality,  data-driven  decision-making,  and  more  efficient  integration  of  medical  systems.